SEXUAL VIOLENCE IN ARMED CONFLICT: ONE-SIDED JUSTICE FOR WOMEN: KEKERASAN SEKSUAL DALAM KONFLIK BERSENJATA: KEADILAN YANG BERAT SEBELAH BAGI PEREMPUAN - Maratussholehah, Hanifah; Fitriliani, Yulia (Fakultas Hukum Universitas Trisakti, 2024)
This paper explores the strategic use of sexual violence in armed conflict and the unequal application of justice for women victims. Drawing on international humanitarian law—including the Geneva Conventions, Additional Protocols, the Rome Statute, CAT, and the ICCPR—it affirms that sexual violence is strictly prohibited in both international and non-international conflicts. However, case studies from Palestine and Israel reveal that these legal protections are often not fully implemented or equitably enforced. Women are frequently subjected to coercion, humiliation, and intimidation, while systemic legal and social barriers hinder their access to justice. The discussion further highlights the limited availability of post-assault healthcare and the inadequate prosecution of perpetrators. The findings suggest that despite the existence of strong legal frameworks, justice remains selective and insufficiently survivor-centered. It is therefore imperative to ensure consistent enforcement of humanitarian and human rights law and adopt a victim-centered approach to eliminate gender-based disparities in accountability and protection